2015
DOI: 10.1152/ajprenal.00200.2015
|View full text |Cite
|
Sign up to set email alerts
|

Increased urothelial paracellular transport promotes cystitis

Abstract: Changes in the urothelial barrier are observed in patients with cystitis, but whether this leads to inflammation or occurs in response to it is currently unknown. To determine whether urothelial barrier dysfunction is sufficient to promote cystitis, we employed in situ adenoviral transduction to selectively overexpress the pore-forming tight junction-associated protein claudin-2 (CLDN-2). As expected, the expression of CLDN-2 in the umbrella cells increased the permeability of the paracellular route toward ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 81 publications
(100 reference statements)
7
39
0
Order By: Relevance
“…Montalbetti et al. showed that, in rats, increased urothelial permeability caused by disrupted urothelial tight junctions resulted in bladder afferent nerve hyperexcitability and upstream central nerve sensitization with few inflammatory changes, and without altering epithelial quantity or umbrella cell polarity/differentiation 130,131 . In contrast, emerging evidence has suggested a potential connection between bladder/pelvic hypersensitivity and psychological/physiological stress, involving functional alteration of the CNS, in humans.…”
Section: Animal Modelsmentioning
confidence: 99%
“…Montalbetti et al. showed that, in rats, increased urothelial permeability caused by disrupted urothelial tight junctions resulted in bladder afferent nerve hyperexcitability and upstream central nerve sensitization with few inflammatory changes, and without altering epithelial quantity or umbrella cell polarity/differentiation 130,131 . In contrast, emerging evidence has suggested a potential connection between bladder/pelvic hypersensitivity and psychological/physiological stress, involving functional alteration of the CNS, in humans.…”
Section: Animal Modelsmentioning
confidence: 99%
“…According to N. Montalbetti et al such urothelial paracellular transport of substances is possible even without damage to the urothelial barrier. [15].…”
Section: Results Of the Research And Their Discussionmentioning
confidence: 99%
“…Although the main role of bladder urothelium is thought to provide a barrier which is impermeable to all urinary solutes, reduced urothelial barrier function has been observed in patients with IC/BPS [40,41]. A recent study in rats has shown altered expression and function of paracellular tight junctions in the urothelium may trigger bladder inflammation and promote cystitis [42].…”
Section: Urothelial Changesmentioning
confidence: 99%
“…Other urothelial associated proteins also contribute to the permeability barrier. These include the uroplakins that form a covering over the urothelial luminal surface [51] and the tight junction proteins that bind the urothelial cells together [42]. In patients with IC/BPS, there is an absence of the tight junction protein zona occludens-1 (ZO-1), and also there are deficiencies in the expression of uroplakin and E-cadherin [40].…”
Section: Urothelial Changesmentioning
confidence: 99%